To determine which equation describes the function in the table correctly, we first need to identify the relationship between \( x \) and \( y \).
Let's look at the changes in \( y \) as \( x \) increases:
- From \( x = 0 \) to \( x = 1 \), \( y \) changes from \(-5\) to \(-9\) (decreases by 4).
- From \( x = 1 \) to \( x = 2 \), \( y \) changes from \(-9\) to \(-13\) (decreases by 4).
- From \( x = 2 \) to \( x = 3 \), \( y \) changes from \(-13\) to \(-17\) (decreases by 4).
The consistent decrease of 4 in \( y \) suggests a linear relationship. The slope \( m \) can be calculated as \( -4 \) (since \( y \) decreases by 4 for every increase of 1 in \( x \)).
Now, we can use the point-slope form of the equation for a line. Starting from the point \( (0, -5) \):
\[ y - y_1 = m(x - x_1) \]
Using \( (0, -5) \):
\[ y + 5 = -4(x - 0) \] \[ y + 5 = -4x \] \[ y = -4x - 5 \]
If we want to express this in function notation, it would be:
\[ f(x) = -4x - 5 \]
Among the options provided:
- \( f(x) = -5x - 4 \) (this doesn't fit)
- \( f(y) = -5x - 4 \) (this doesn't fit)
- \( f(x) = -4x - 5 \) (this fits)
Therefore, the correct equation is:
f(x) = -4x - 5